A comparison of voluntary and mandatory adoption of Radio Frequency Indentification (RFID) technology in organizations - Hossain, M.; Quaddus, Mohammed (World Business Institute Australia, 2011)
The purpose of this study is to compare the organizational adoption factors of Radio Frequency Identification (RFID) between adopters and non-adopters in mandatory and voluntary environments respectively. This paper presents the result of an empirical study that investigates the adoption behaviour of livestock farms in relation to RFID technology adoption in the context of Australia. The quantitative research approach has been taken for this study. The finding of this study confirmed that external pressure and organizations’ management-related factors are considered as significant by both adopters and non-adopters. Moreover, adopters considered that compatibility is another important factor for RFID adoption; while the non-adopters emphasized on costs of and expected-benefits from RFID. Implications of the results are discussed.